Model Pengembangan Tenaga Kerja Lokal dalam Meningkatkan Perekonomian dan Menunjang Pariwisata Desa Wisata Saba Kecamatan Blahbatuh Kabupaten Gianyar - Desak Gde Dwi Arini; Putu Ayu Sriasih Wesna; Nengah Ganawati (Fakultas Hukum, Universitas Warmadewa, 2024)
The legal protection of local workers in the Law of the Republic of Indonesia Number 13 of 2003 concerning Manpower and Regional Regulation (Perda) of Bali Province Number 10 of 2019 concerning the implementation of Manpower, Law Number 10 of 2009 concerning Tourism, Regional Regulation of Bali Province Number 5 of 2020 concerning Standards for Organizing Balinese Cultural Tourism, in companies located in Saba Tourism Village, Blahbatuh District, Gianyar Regency is a study of researchers. Companies located in Saba Tourism Village, Blahbatuh District, Gianyar Regency employ local workers in all fields, and it is highly expected that the Government in general and employers as investors and local workers in particular that arrangements regarding legal protection and local labor development models require separate policies from employers, where the employer is also obliged to foster good relations with all parties, namely investors, the Saba Tourism Village community and the Government of Gianyar Regency, because the policies and regulations issued by the company are inseparable from its supervision, to avoid the possibility of arbitrary actions by employers against the local workforce itself. The method used is empirical legal research, with primary data through field research, secondary data through library research. The purpose of this study is to examine and analyze the local workforce development model in the Company located in Saba tourist attraction Blahbatuh District Gianyar Regency, as well as the constraints and obstacles faced by a company in applying the legislation. From the research results obtained that the local labor development model seen from the condition of the internal factors of local labor development in improving the economy of the Saba tourist village community is still greater than the weakness factors, while the condition of external factors is still greater than the opportunity factor threat. The local workforce development strategy in improving the economy is a wearknes-opportunity (WO) strategy, namely improving the skills of local workers in the formal or informal sector, especially for local workers, then improving facilities and infrastructure and supporting human resources (HR), the employment training center (BLK) for training and improving the business skills of local workers in various sectors, accelerating services and prioritizing business investment rules so that they can absorb more local labor. While the empowerment of local labor in the Krisna souvenir business, Ajik's milk pie business, Aloe Vera business, Villa and Restorant business, Turtle Breeder business, Plaminggo business located in the Saba tourist village, Gianyar Regency, in accordance with the Bali Provincial Regional Regulation Number 10 of 2019 concerning the implementation of Manpower has agreed with the Blangsinga traditional village to coordinate with the Customary Village and it has been agreed to employ local labor around 70% from local labor in the Blangsinga traditional village, and 30% from outside labor. This shows that the local workforce recruited comes from their birthplace or is native to the area where they live and are domiciled in the area and are proven by identity cards (KTP) and family cards (KK). As well as the role of traditional villages in empowering local labor is very large, very influential on the company's commitment and there must be approval from the traditional village every time they recruit workers, with the aim that there is a balance between the rights and obligations of companies operating in the village which contributes to the welfare of the surrounding community and automatically provides welfare from the economic aspect. The targeted scientific journal output is a Sinta 4 Accredited National Journal entitled KertaWicaksana Journal, as well as a 2024 research report, and Intellectual Property Rights (IPR).